EFEKTIVITAS MICRO TEACHING DALAM MENINGKATKAN KETERAMPILAN MENGAJAR: TINJAUAN LITERATUR - Ginting, Rahmadani Fitri; Hamidah, Nurul (Sindoro: Cendikia Pendidikan, 2024)
This research aims to determine the effectiveness of micro teaching in improving the teaching skills of prospective teachers through a literature review. Using a literature study approach, this research explores various views from books and academic journals regarding micro teaching, as well as its impact on the development of teaching competence. The study results show that micro teaching is effective in strengthening basic teaching skills such as lesson planning, classroom management, and communication. This article also discusses the benefits and limitations of implementing micro teaching based on the results of previous research.